2016
DOI: 10.1352/1934-9556-54.4.285
|View full text |Cite
|
Sign up to set email alerts
|

“My Voice Counts, Too”: Voting Participation Among Individuals With Intellectual Disability

Abstract: Despite a strong societal commitment to ensuring that individuals with intellectual disability (ID) fully participate in their communities, few people with ID vote. Little is known about voting experiences from the perspective of people with ID. In-person, semistructured interviews were conducted with 28 adults with ID (Mage = 37 years) to obtain their input on voting. Constant comparison and content analysis methods were used to characterize themes. Results indicated that people with ID are interested in voti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…People with physical, intellectual, and psychological disabilities have lower rates of voting. Agran, MacLean, and Kitchen found lower voting rates in communities of people with intellectual disabilities [28]. Matsubayashi and Ueda [33], Mattila and Papageorgiou [34], and Shields, Schriner, and Schriner [37] discovered low voter turnout rates among people with disabilities, with barriers to voting including discrimination and accessibility.…”
Section: Differences In Voter Participation Are Associated With Healtmentioning
confidence: 99%
“…People with physical, intellectual, and psychological disabilities have lower rates of voting. Agran, MacLean, and Kitchen found lower voting rates in communities of people with intellectual disabilities [28]. Matsubayashi and Ueda [33], Mattila and Papageorgiou [34], and Shields, Schriner, and Schriner [37] discovered low voter turnout rates among people with disabilities, with barriers to voting including discrimination and accessibility.…”
Section: Differences In Voter Participation Are Associated With Healtmentioning
confidence: 99%
“…Self-Advocacy. In prior research, self-advocacy was an important tool in supporting people with IDD to recognize and exercise their rights, including the right to vote (Agran et al, 2016;Anderson & Bigby, 2015). Participating in self-advocacy events supported decision making, confidence, and the development of a positive social identity (Anderson & Bigby, 2015).…”
Section: Participationmentioning
confidence: 99%
“…As many of their clients never expressed an interest in voting, they (service providers) "never considered the idea." In a follow-up study involving a different sample of support personnel, Agran, MacLean, and Kitchen (2016) reported that 80% of the respondents indicated that their clients never expressed an interest in voting; 86% indicated that parents, guardians, or advocates never discussed voting at planning meetings; approximately 66% of the clients were not registered to vote; 81% of the support personnel never assisted clients to register to vote; and 79% never provided any voting instruction.…”
Section: Extent To Which Service Has Been Implementedmentioning
confidence: 99%